An observational study on treatment regimens and effectiveness for psoriasis in real-world settings among 407 patients in Southeast China - Huo, Yuping; Huang, Yike; Lee, Tungchun; Lin, Maoying; Chun, Wenhung (Frontiers in Medicine, 2024)
Introduction While new targeted therapies have advanced psoriasis treatment, real-world data on comparative effectiveness is lacking. This study analyzed treatment regimens and response in an observational cohort, examining potential disparities between clinical trials and routine practice. Methods Data from the Psoriasis Standardized Diagnosis and Treatment Center registry were analyzed. Patients with ≥1 follow-up were included. Treatment response was assessed using PASI 50/90 criteria. Factors associated with response were analyzed. Results 407 patients were included (46 first-time diagnosed, 361 previously diagnosed). A higher proportion of first-time diagnosed patients achieved treatment response than previously diagnosed (76.1% vs. 62.6%). Multivariable analysis identified factors associated with reduced response in previously treated patients. Conclusion This real-world study found lower treatment response rates compared to clinical trials, especially in previously treated patients. Disparities highlight remaining unmet needs for psoriasis management. Combination and rotational strategies may improve outcomes in patients unresponsive to available therapies. Ongoing research on novel targets and pathways is warranted to address treatment gaps.